2006
DOI: 10.1093/aje/kwk018
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Prevalent and Incident Urinary Incontinence in a Cohort of Midlife Women: A Longitudinal Analysis of Data: Study of Women's Health Across the Nation

Abstract: To compare the characteristics of and baseline factors associated with prevalent and incident urinary incontinence in a diverse cohort of midlife women, the authors analyzed the baseline and first five annual follow-up visits of the Study of Women's Health Across the Nation (SWAN), 1995-2001. From responses to annual questionnaires, the authors defined prevalent incontinence as at least monthly incontinence reported at baseline and incident incontinence as at least monthly incontinence first reported over foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
208
8
20

Year Published

2008
2008
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 224 publications
(252 citation statements)
references
References 18 publications
16
208
8
20
Order By: Relevance
“…12,13,16,17 Although BMI has been most closely linked with stress incontinence, only a handful of studies have shown an association with urge incontinence in women. 8,15,35 In this study, the raised risk of urge incontinence was only restricted to women who were obese at the age 36 and 43 years and was considerably attenuated in the fully adjusted model. As it has been described previously, 11 this may be that both are due to a common underlying 'anxiety state'.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…12,13,16,17 Although BMI has been most closely linked with stress incontinence, only a handful of studies have shown an association with urge incontinence in women. 8,15,35 In this study, the raised risk of urge incontinence was only restricted to women who were obese at the age 36 and 43 years and was considerably attenuated in the fully adjusted model. As it has been described previously, 11 this may be that both are due to a common underlying 'anxiety state'.…”
Section: Discussionmentioning
confidence: 69%
“…8 From the Study of Women across the Nation, it was found that women who were overweight at baseline (mean age 45.8 years) had a higher risk of developing incontinence over the next 5 years. 8 However that study did not consider BMI at earlier ages or include confounders across the life course. A number of crosssectional studies have also found a significant association between BMI and incontinence, but have not distinguished between symptoms of stress or urge incontinence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the longitudinal studies of community-dwelling older adults, risk factors for incident incontinence in men and women include age and impairment in functional status. 2,3 Among women, estrogen, 4,7 hysterectomy, 4 and increased body mass index 6 correlated with incident incontinence. White race/ethnicity has been associated with an increased risk of incident incontinence in women, 4 whereas among peri-menopausal women, African American race/ethnicity was a risk factor for increased urge incontinence.…”
Section: Introductionmentioning
confidence: 98%
“…White race/ethnicity has been associated with an increased risk of incident incontinence in women, 4 whereas among peri-menopausal women, African American race/ethnicity was a risk factor for increased urge incontinence. 6 The purpose of this study was to determine the incidence of urinary incontinence in older adults and examine potential risk factors associated with the development of incontinence over a three-year period, as part of the University of Alabama at Birmingham (UAB) Study of Aging. 8 …”
Section: Introductionmentioning
confidence: 99%